Accessibility Improvement Models for Typical Flats: Mass-Customizable Design for Individual Circumstances. Issue 3 (2nd July 2016) - Kaasalainen, Tapio; Huuhka, Satu
ABSTRACT: Elderly housing policies in Finland emphasize aging in place and preparing the existing housing stock for the predicted increase in the aged population. Timely home modifications that enhance mobile accessibility are a focal target for these policies. This article introduces the idea of mass-customizable architectural accessibility improvement models (AIMs) that have been developed for typical Finnish flats. The applicability and generalizability of an AIM designed for an archetypal two-room flat is tested by applying it to nine case buildings in the city of Tampere. The model was found to be beneficial for 42 of the 45 rooms in the research material.